Kontrowersje pomiędzy neo-neoklasykami a neokeynesistami wokół teorii kapitału - Żurawicki, Leon (Wydział Prawa i Administracji UAM, 1975)
The theory of capital has been developed on the basis of discussions on the origin and process of economic growth. This theory concerns the problem of the role of capital in the economic growth and the approaches to the measurement of its influence upon the economic growth. It is also the essential problem of the discussion between the New-Newclassicists and New-Keynesians. Within the problem, there is a question, whether capital, like labor, can be considered as the production factor.
A Controversy Between the New-Newclassicists and New-Keynesians as Concerns the Theory of Capital